1995
DOI: 10.1152/ajpgi.1995.268.3.g496
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial buffer capacity influences Na+/H+ exchange kinetics and oxyntic cell pHi in intact frog gastric mucosa

Abstract: We studied the influence of interstitial buffer capacity and CO2-HCO3- on oxyntic cell intracellular pH (pHi) in intact frog gastric mucosa. Oxyntic cells in stripped gastric mucosa of Rana esculenta were loaded with the pH-sensitive dye 2',7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein, and pHi was assessed fluorometrically. In the presence of a constant serosal and luminal pH, oxyntic cell pHi was dependent on the serosal but not the luminal concentration of cell-impermeable buffer ions such as N-2-hydroxyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Apical localization would lead to proton extrusion into the lumen, which is not observed in Ussing chamber experiments where acid secretion is completely inhibited by omeprazole (P. Song, unpublished observations). Other theoretical considerations and functional results are supportive of basolateral NHE2 expression: NHE2 is strongly upregulated by extracellular alkalinity, which likely occurs in the interstitial space during acid secretion (Seidler et al 1995). As a possible correlate, Na + /H + exchange activity is increased in frog gastric mucosa upon serosal alkalization.…”
Section: Ph I and Volume Homeostasis During Acid Secretionmentioning
confidence: 72%
See 1 more Smart Citation
“…Apical localization would lead to proton extrusion into the lumen, which is not observed in Ussing chamber experiments where acid secretion is completely inhibited by omeprazole (P. Song, unpublished observations). Other theoretical considerations and functional results are supportive of basolateral NHE2 expression: NHE2 is strongly upregulated by extracellular alkalinity, which likely occurs in the interstitial space during acid secretion (Seidler et al 1995). As a possible correlate, Na + /H + exchange activity is increased in frog gastric mucosa upon serosal alkalization.…”
Section: Ph I and Volume Homeostasis During Acid Secretionmentioning
confidence: 72%
“…While Waisbren et al (1994) microdissected and luminally perfused gastric glands and found a very low apical proton permeability, Kaneko et al (1991) observed a rather profound decrease in surface cell pH i upon luminal acid perfusion in the rat stomach in vivo, which was further enhanced by Na + /H + exchange inhibition with an amiloride analogue (Kaneko et al 1992). Interestingly, this pH i decline was strongly dependent on interstitial buffer capacity, and a high interstitial buffer capacity was essential for the gastric epithelial cells to regulate their pH i (Stumpf et al 1993, Seidler et al 1995. We stepwise decreased luminal pH in isolated frog gastric mucosa and found no change in pH i down to a luminal pH of 3, but at pH 2, surface cell pH i decreased slightly to a new pH.…”
Section: Ph I Maintenance In Gastric Epithelial Cells During An Acid mentioning
confidence: 99%
“…33,34 We had previously noticed that a high interstitial buffer capacity is essential for proper pH i control of the gastric surface cells, because protons that are extruded through the basolateral membrane, via the Na + /H + exchange, need to be rapidly removed from that location. 35 The effect of interstitial buffer capacity on pH i was detected even with a neutral pH in the lumen, but was strongly enhanced when the luminal pH was decreased. We had therefore hypothesized that cellular pH i regulatory mechanisms are necessary for gastric acid resistance, but can only function optimally in the presence of high interstitial buffering capacity, augmented by bloodborne CO 2 /HCO À 3 .…”
Section: Discussionmentioning
confidence: 98%
“…We had previously noticed that a high interstitial buffer capacity is essential for proper pH i control of the gastric surface cells, because protons that are extruded through the basolateral membrane, via the Na + /H + exchange, need to be rapidly removed from that location 35. The effect of interstitial buffer capacity on pH i was detected even with a neutral pH in the lumen, but was strongly enhanced when the luminal pH was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work identified at least isoforms 1-4 in mucous, endocrine, and parietal cells of the rabbit, rat, and mouse stomach (2,17,19,22). Whereas the role of the NHE-1, -2, and -4 isoforms in the stomach have been addressed in several studies (2,19,21), the role and localization of the NHE-3 isoform has not been examined in detail.…”
mentioning
confidence: 99%